Pegaruh Kepemimpinan dan Penempatan Kerja terhadap Kinerja Pegawai Melalui Komitmen Pegawai pada Badan Pengembangan Sumber Daya Manusia Provinsi Riau - Asnawi, Wawan; Isyandi; Machasin (Program Studi Manajemen FEBM UMRAH, 2024)
This study aims to determine and analyze leadership and work placement on employee commitment. To analyze the influence of Leadership and Work Placement on employee performance. To analyze the effect of leadership on employee performance through commitment. To analyze the influence of Job Placement on employee performance through employee commitment. To analyze the influence of employee commitment to employee performance. In this study, the population consisted of 106 civil servant employees. While the sample used was 106 people. The data used in this study are primary data and secondary data, while the data collection technique uses a questionnaire. The data analysis technique used in this study is the data analysis used in this study is SEM. Leadership influences commitment. Work placement affects commitment. Leadership influences performance. Work placement affects performance. Leadership has a significant effect on employee performance through commitment. Work placement has a significant effect on employee performance through commitment. Commitment has a significant effect on employee performance.